2010
DOI: 10.1037/a0018168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an intensive depression-focused intervention for smoking cessation in pregnancy.

Abstract: Objective-The objective of this study was to evaluate a depression-focused treatment for smoking cessation in pregnant women, versus a time and contact health education control. We hypothesized that the depression-focused treatment would lead to improved abstinence and reduced depressive symptoms among women with high levels of depressive symptomatology. No significant main effects of treatment were hypothesized.Method-Pregnant smokers (N=257) were randomly assigned to a 10-week intensive depressionfocused int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 59 publications
1
119
0
Order By: Relevance
“…Three studies in this special section utilize theory-based treatments that have demonstrated effectiveness in other areas of health behavior change and apply them to smoking cessation (Borrelli et al, 2010;Cinciripini et al, 2010;MacPherson et al, 2010). Although these articles report the main effects of treatment on smoking cessation, more research is needed on the mechanisms of change so that intervention targets can be more accurately pinpointed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies in this special section utilize theory-based treatments that have demonstrated effectiveness in other areas of health behavior change and apply them to smoking cessation (Borrelli et al, 2010;Cinciripini et al, 2010;MacPherson et al, 2010). Although these articles report the main effects of treatment on smoking cessation, more research is needed on the mechanisms of change so that intervention targets can be more accurately pinpointed.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on affect and smoking has focused almost exclusively on the role of negative affect, but positive affect has also shown a strong association with treatment outcome (al'Absi, Hatsukami, Davis, & Wittmers, 2004;Doran et al, 2006). Similarly, Cinciripini et al (2010) in this issue apply a treatment typically used for the treatment of chronic depression to help pregnant smokers quit. Study participants received 10 individual counseling sessions of smoking cessation plus the Cognitive Behavioral Analysis System of Psychotherapy (CBASP; McCullough, 2000), which focused on interpersonal stress and on increasing the quality of one's relationship with significant others or they received smoking cessation plus health and wellness.…”
Section: Testing New Theoretical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Smoking is one of the major modifiable risk factors, responsible for the premature death of nearly 6 million people worldwide and considerable economic costs to health systems (1)(2)(3). Among women, smoking is associated with an increased risk of breast cancer, cervical cancer, ovarian cancer, infertility, and early menopause (4).…”
Section: Introductionmentioning
confidence: 99%